Policy Implementation on Employee Effectiveness and Implications on Society Satisfaction in Regional General Hospital Type C at Tasikmalaya District and Ciamis District - Aceng Solahudin Ahmad; Kamal Alamsyah; Achdiat Achdiat (Doctoral Program of Social Science Pasundan University, 2020)
This research's problem is related to employees' work effectiveness, which is still low and has implications for the low level of community satisfaction at RSUD type C in Tasikmalaya Regency and Ciamis Regency for both out and inpatients. It is thought to be related to implementing the Minimum Service Standards policy that has not been running optimally. Minimum Service Standards (SPM) are provisions regarding the type and quality of essential services mandatory regional affairs to which every citizen is entitled to a minimum. This study uses a descriptive analysis method; While the approach used in this research is quantitative. The research conducted found that the impact of policy implementation on the work effectiveness of employees was quite significant and had implications for community satisfaction at Type C Regional General Hospitals in Tasikmalaya and Ciamis Regencies (54.3%). It implies that implementing the Minimum Service Standards policy is quite dominant and determines the increase in employee work effectiveness and impacts on community satisfaction. This study also found that the increase in work effectiveness and its implications for community satisfaction were determined by the implementation of the MSS policy and other variables not studied (45.7%). Therefore, the implementation of the policy has a positive impact on the work effectiveness of employees at Type C Regional General Hospitals in Tasikmalaya and Ciamis Regencies (31.95). Therefore, it can be interpreted that the implementation of the Minimum Service Standards policy has contributed quite dominantly to the improvement of employee work effectiveness. The dimensions of policy implementation that have the most significant impact on employee work effectiveness are the dimensions of the disposition or attitude of the implementers (6.1%). The dimensions of little influence are the social, economic, and political environment (4.1%). The study results also found that the implementation of the policy indirectly had a positive impact on community satisfaction at the Type C Regional General Hospital in Tasikmalaya and Ciamis Regencies (44.7%). It can be interpreted that the implementation of the Minimum Service Standards policy provides a very dominant contribution to the level of community satisfaction. The dimensions of policy implementation that have the most significant impact on community satisfaction are the dimensions of the disposition or attitude of the implementers (6.1%). At the same time, the dimensions with little influence are the dimensions of the social, economic, and political environment (4.1%). Employee work effectiveness positively impacts community satisfaction at Type C Regional General Hospitals in Tasikmalaya and Ciamis Regencies (35.4%). It can be interpreted that the effectiveness of employees' work provides a very decisive contribution to community satisfaction. The dimensions of employee work effectiveness that have the most significant impact on community satisfaction are punctuality at work (14.4%), while the dimension with little influence is the dimension of quality accuracy at work (9.6%).